Veterinary Sciences and One Health approach in pandemic times (FAVE Sección Ciencias Veterinarias, 2021)
The veterinary sciences emerged and developed to address interests and demands of society in which animal health was highly relevant. At the time when Claude Bourgelat founded the first veterinary schools in France (Lyon in 1761; Alfort in 1764), the necessity that drove the initiative were sanitary problems of animal species that played very important roles for society: horses and cattle. In those beginnings of the discipline, Bourgelat's vision was pioneer and of vanguard, adopting perspectives that are currently boosted by scientific disciplines: comparative, interdisciplinary and integrative approaches (Wake, 2003).As years went by, other demands and interests concerning animal health arose, involving other animal species. Thus, veterinary sciences expanded their scope, gradually becoming a source of knowledge highly relevant for animal husbandry and welfare, public health, and conservation of wildlife species. During this evolution, veterinary sciences accompanied the development of biomedical sciences recognizing that life in our planet occurs with dynamics dictated by webs of interactions among organisms of different species that share the same environments. This complex inter-relationship between the components of the planetary system determines that a significant disruption of some elements affects the rest directly or indirectly, in a low or high level of magnitude, impacting the system's functioning. This understanding is the cornerstone upon which is based the construction of the web of knowledge on health and disease that feeds and consolidates the concept of 'One Health'.The 'One Health' approach acknowledges the interconnection between people and the remaining forms of life, and with the environments they share, and have as a main goal the improvement of global health by means of a collaborative, multisectoral, and transdisciplinary approach, acting at the local, regional and global levels (Karesh & Cook, 2009). This concept becomes paramount when taking into account that most diseases affecting humans in the last decades have been caused by pathogens originated in animals (Taylor et al.,2001; Jones et al., 2008).Although the 'One Health' perspective has become increasingly important in recent years, the concept has more than half a century of evolution, and it has deep veterinary roots. In 1964, Dr. Calvin Schwabe, a veterinary epidemiologist, coined the concept of 'One Medicine', in his book 'Veterinary Medicine and Human Health'. Decades later, the veterinarian William Karesh installed the notion of 'One World, One Health', and that idea gained thrust when the 'Centers for Disease Control' of USA established its 'One Health Office' in 2009. This approach recognizes the inextricable links between people and nature, and envisages the health and disease phenomenon from an integrative angle.The relevance and importance of this concept was highlighted during the current pandemic. A coronavirus that naturally circulates in some wild animals adapted to humans and began worldwide propagation. Infected people may transmit the virus to cats, dogs, hamsters, large cats, ferrets, minks, gorillas, and other animals. Minks first infected by people then became a source of contagion for other people. Epidemiologic studies in mink farms shed light on the transmission dynamics of the novel virus. Current knowledge on virus dynamics in nature helps us to better understand and anticipate the patterns of infection by SARS-CoV-2. Many animal species are used as models to conduct experiments to understand, prevent and control COVID-19. Our current relationship with nature is scrutinized, and the causes and risk factors with the potential of unleashing new pandemics are investigated. The way mankind comprehends the health and disease phenomenon has changed forever.
Keywords: One Health; Veterinary Medicine; Integrative approach; Comparative approach